Domain function and predicted structure of three heterodimeric endonuclease subunits of RNA editing catalytic complexes in Trypanosoma brucei. Issue 17 (12th September 2022) - Carnes, Jason; McDermott, Suzanne M; Lewis, Isaac; Tracy, Maxwell; Stuart, Kenneth
Abstract: Each of the three similar R NA E diting C atalytic C omplexes (RECCs) that perform gRNA-directed uridine insertion and deletion during Trypanosoma brucei  mitochondrial (mt) mRNA editing has a distinct endonuclease activity that requires two related RNase III proteins, with only one competent for catalysis. We identified multiple loss-of-function mutations in the RNase III and other motifs of the non-catalytic KREPB6, KREPB7, and KREPB8 components by random mutagenesis and screening. These mutations had various effects on growth, editing, and both the abundances and RECC associations of these RNase III protein pairs in bloodstream form (BF) and procyclic form (PF) cells. Protein structure modelling predicted that the Zinc Finger (ZnF) of each paired RNase III protein contacts RNA positioned at the heterodimeric active site which is flanked by helices of a novel R Nase III-A ssociated M otif (RAM). The results indicate that the protein domains of the non-catalytic subunits function together in RECC integrity, substrate binding, and editing site recognition during the multistep RNA editing process. Additionally, several mutants display distinct functional consequences in different life cycle stages. These results highlight the complementary roles of protein pairs and three RECCs within the complicated T. brucei mRNA editing machinery that matures mt mRNAs differentially between developmental stages.